Patient-centered nutrition education improved the eating behavior of persons with uncontrolled type 2 diabetes mellitus in North Ethiopia: a quasi-experimental study - Gebreyesus, Hagos Amare; Abreha, Girmatsion Fisseha; Beshirie, Sintayehu Degu; Abera, Merhawit Atsbha; Weldegerima, Abraha Hailu; Bezabih, Afework Mulugeta; Lemma, Tefera Belachew; Nigatu, Tsinuel Girma (Frontiers in Nutrition, 2024)
Background: Improving the clinical outcome of people with type 2 diabetes mellitus by modifying their eating behavior through nutrition education is an important element of diabetes self-management. Significant data from the literature supports this idea, however in the Ethiopian setting, there is a practice gap. Therefore, the purpose of this study was to assess how patient-centered nutrition education affected the eating behavior and clinical outcomes of people with uncontrolled type 2 diabetes mellitus.In this quasi-experimental trial, 178 people with uncontrolled type 2 diabetes were purposely assigned to the intervention (n=89) or control (n=89) arm. The intervention arm was given patient-centered nutrition education, wheras the control arm received the routine care.Eating behavior and clinical outcome indicators such as HbAc, lipid profile, anthropometric indices, and blood pressure were assessed in both groups at the start and completion of the intervention. All scale variables were tested for normality and log transformed when appropriate.The baseline characteristics of the intervention and control groups were compared using the t-test for continuous variables and the chi-square test for categorical variables. The effect of nutrition education was determined using a difference in differences (DID) approach. P < 0.05 was established as the criterion of significance.Result: Food selection (DID = 15.84, P 0.001), meal planning (DID = 31.11, P 0.001), and calorie needs (DID = 37.65, P 0.001) scores were statistically higher in the nutrition education arm. Furthermore, their overall eating behavior score (DID = 27.06, P 0.001) was statistically greater than the controls. In terms of clinical outcomes, the overall picture reveals that the intervention did not outperform over the routine care. However, in comparison to the controls, the intervention arm showed clinically significant improvement in HbA1c (DID = -0.258, P = 0.485).Patient-centered nutrition education has resulted in positive adjustments in the eating behavior of people with uncontrolled type 2 diabetes mellitus. Furthermore, it has shown a great potential for improving their glycemic control.